Conditioning care: Universal Assignation for Social Protection by Child in Argentina - Pautassi, Laura (2014)
The article examines the links between the social organization of caregiving and factors in health and education for infants and adolescents that are required, especially of mothers who benefit from policies for income transfers. With this objective, we focus on the Universal Assignation for Social Protection by Child (AUH, for its abbreviation in Spanish) in Argentina, which has received little study within a gender focus and, even less so, from a view of caregiving and the differentiated responsibilities in a couple. Taking into account interviews of state actors and receiving mothers, as well as an analysis of norms, institutional documents, and other studies about this policy, the analysis concentrates on the impact of AUH on women and the dynamics of caregiving. Among the principal findings of the study, tensions are identified among academic critics of appointments and of conditions and the form in which the receiving women live and evaluate the design.